Analysis of the legal treatment of human conscience: reflections on Brazilian constitutionalism (Research, Society and Development, 2022)
Conscientious objection protects the principle of respect for full and conscious autonomy and freedom, which is among the fundamental rights provided for in the Brazilian Federal Constitution of 1988, however, it is common for the matter to be absorbed by legal and civil society, due to of a certain lack of knowledge on the part of the operators of the law and the difficulty of implementation on the part of the State. Conscientious objection could be summarized concisely as a conscious non-adherence to a certain norm or act due to the conscience of the individual. However, the question is: Would it be acceptable for someone, based on their own principles, to harm another person? Can someone be forced to act in a certain way, even if it is against their values ​​to the detriment of the well-being of others? In this way, the main objective of this study is summarized in pointing out the access to the right of conscientious objection in Brazil, as well as demonstrating in the light of bioethics and law, the meaning given by the legal system to the institute, seeking to reach a conclusion about of the most correct position to be taken by the State in the face of a possible conflict of fundamental principles and rights. It is concluded that the objection cannot be based on personal whims, so that the reasons are proportional to the values discussed, and that the objector is willing to have a possible dialogue seeking an efficient or less burdensome solution, thus seeking to ensure that the objection does not conflict with the rights of other individuals, especially with regard to the right to life.